Malaysian anti-terrorism efforts & Islamic criminal justice system: a comparative appraisal - Mohamad Yunus, Mohamad Ismail; Nik Rahim, Nik Wajis; Mohamad Hanifa, Shamshina (Institute Public Security of Malaysia - IPSOM, 2017)
In general, sense, terrorism is the use of intentional and indiscriminative violence as a means to create terror or fear, in order to achieve a political, religious, or ideological aim. It is used in this regard primarily to refer to violence against civilians or non-combatants. Although the term has been in use since at least the 1970s, it initially became popular when journalists and politicians publicly introduced and started using the term “Islamic terrorists” following the September 11 attacks. Rather than being used to describe a type of activity, the term has often been used politically as a term of abuse or denunciation, both by insurgent groups and by governments against each other. There is no universally agreed upon definition of the term, and many definitions exist. Thus, the article will focus on the legal issues of the terrorism in Malaysia and under the Islamic criminal law perspective. The second issue is on the enhancement of the enforcement of public safety and security, the priority to protect the country from being attacked by the terrorists. Lastly, the community roles in preventing themselves from being influenced by terrorists. Without the full support and cooperation of the community to government security agencies, the safety and security of the country may not be effectively secured.